1991
DOI: 10.1182/blood.v77.10.2214.2214
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte colony-stimulating factor in cerebrospinal fluid from patients with meningitis

Abstract: Granulocyte colony-stimulating factor (G-CSF) in the cerebrospinal fluid from patients with meningitis was measured by our modified enzyme- linked immunosorbent assay for G-CSF. The minimal detection level was 20 pg/mL G-CSF. In patients with bacterial meningitis, the G-CSF levels in the cerebrospinal fluid were extremely elevated, showing a mean value of approximately 1,500 pg/mL. On the other hand, G-CSF levels in the cerebrospinal fluid from 67% patients with aseptic meningitis were moderately increased, sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

1992
1992
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 14 publications
1
11
1
Order By: Relevance
“…Unlike other cytokines such as TNF-␣ or IL-1 in another experiment [23], G-CSF injected i.c. did not cause migration of leucocytes into the subarachnoid space, although the concentrations which were presumably present in the CSF in this study (Ϸ 5 g/ml and 1 g/ml) assuming a CSF volume of 2 ml, were substantially higher than those observed in humans with bacterial meningitis (mean Ϸ 1500 pg/ml [6]). For this reason, G-CSF in CSF appears not to be directly involved in granulocyte recruitment or at least will not be the only substance being responsible for the recruitment of granulocytes.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…Unlike other cytokines such as TNF-␣ or IL-1 in another experiment [23], G-CSF injected i.c. did not cause migration of leucocytes into the subarachnoid space, although the concentrations which were presumably present in the CSF in this study (Ϸ 5 g/ml and 1 g/ml) assuming a CSF volume of 2 ml, were substantially higher than those observed in humans with bacterial meningitis (mean Ϸ 1500 pg/ml [6]). For this reason, G-CSF in CSF appears not to be directly involved in granulocyte recruitment or at least will not be the only substance being responsible for the recruitment of granulocytes.…”
Section: Discussioncontrasting
confidence: 65%
“…G-CSF, and after migration into the central nervous system, release larger amounts of TNF and IL-1␤ into the CSF than leucocytes not activated by G-CSF. In humans, in the CSF increased levels of G-CSF were observed both in bacterial [6,21] and viral [22] central nervous system infections. Unlike other cytokines such as TNF-␣ or IL-1 in another experiment [23], G-CSF injected i.c.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to stimulation with GM-CSF or M-CSF, microglial cells do not proliferate in response to G-CSF . G-CSF is also detected in the CSF of patients with meningitis (Shimoda et al, 1991).…”
Section: Central Nervous Systemmentioning
confidence: 99%
“…A variety of cytokines play critical roles in local inflammatory responses in bacterial and aseptic meningitis [3][4][5][6]. We [7][8][9][10] and other investigators [3][4][5][6]11] showed that levels of the following cytokines increase in the cerebrospinal fluid (CSF) of aseptic meningitis: IL-1, IL-6, IL-10, interferon-gamma (IFN-g), macrophage inflammatory protein-1a (MIP-1a) and colony-stimulating factors, but not TNF-a. Aseptic meningitis is characterized by an initial accumulation in the CSF of neutrophils followed by an elevation of mononuclear cells [8,9].…”
Section: Introductionmentioning
confidence: 96%